Slope Instability Evaluation Using Geophysical Methods of Gua Musang-Cameron Highland Highway - M.T Zakaria; N.M Muztaza; H. Zabidi; F. Ahmad; T.O Adeeko; N Ismail; N Samsudin (Lowland Technology International, 2020)
Slope failure is a complex phenomenon that may trigger theoccurrence of slope failure due to several factors. The internalstructures and mechanical properties of subsurface areimportant parameters to investigate as a pre-requisite analysis.Four parallel survey lines of 2-D resistivity and two lines ofseismic refraction were designed in order to achieve theobjectives. The model shows the resistivity values covered of 1-4000 Ωm with investigation depth of 20 m. Highly weatheredzones were identified at values of 400-450 Ωm while saturatedzones with values of <100 Ωm. The high resistivity regions withvalues of 1500-2500 Ωm indicates the weathered granite for thisarea. The 2-D seismic refraction model shows velocity valuesranging between 200-2800 m/s and depth coverage about 30 m.The result interpreted as 3 layer cases with 1st layer, 2nd layer,and 3rd layer identified at velocity of 400-600 m/s, 800-1400 m/sand >2000 m/s respectively. The low resistivity and velocityindicate as highly fractured/crack zones which able to decreasesthe shear strength of the slope soils and increases the hydraulicconductivity of the soils. The saturated zone and infiltration withthe existence of boulders indicates the factor for the occurrenceof slope failure.